MCDHF calculations and study of plasma parameters for Li-like ions. (June 2016) - Khatri, Indu; Goyal, Arun; Aggarwal, Sunny; Singh, A.K.; Man Mohan,
Abstract: Extensive configuration interaction calculations for several Li-like ions ( Z =32, 36, 42, 46, 50, 54 and 56) are performed using the code GRASP2K based on the multiconfiguration Dirac–Hartree–Fock (MCDHF) method. Breit interaction and leading quantum electrodynamical (QED) effects are also included by applying active-space techniques to enlarge the configuration set. Results for fine-structure energy levels for 1s 2 2p, 1s 2 3s, 1s 2 3p and 1s 2 3d configurations with relative to ground states 1s 2 2s are presented. The wavelengths, transition rates and oscillator strengths for the 1s 2 2s 2 S1/2 –1s 2 2p P 1 / 2, 3 / 2 0 2, 1s 2 2p P 1 / 2, 3 / 2 0 2 –1s 2 3s 2 S1/ 2, 1s 2 2p P 1 / 2 0 2 –1s 2 3d 2 D3/ 2, 1s 2 2p P 3 / 2 0 2 –1s 2 3d 2 D5/ 2 and 1s 2 2s 2 S1/ 2 –1s 2 3p P 1 / 2, 3 / 2 0 2 transitions are reported. Our calculated results are in good agreement with previous theoretical results and compiled values of the National Institute for Standards and Technology (NIST). We have also provided the line intensity ratios and plasma parameters for optically thin plasma. Our calculated data may be useful for experimentalists in identifying the fine-structure levels, for plasma modeling, astrophysical research applications. Highlights: Calculations for several Li-like ions are performed based on the MCDHF method. Results for fine-structure energy levels for 1s 2 2p, 1s 2 3s, 1s 2 3p and 1s 2 3d relative to 1s 2 2s are presented. The wavelengths, transition rates and oscillator strengths for some E1 transitions are reported. Line intensity ratios and plasma parameters for optically thin plasma are calculated.